KOSAKATA PENGUKURAN DALAM BAHASA MELAYU DIALEK SAMBAS - Hidayat, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is describes the measurement in the vocabulary of the Malay language in one Sambas dialect districts in Sambas district. This research focuses on the observation of objects of culture, namely the measurement. This measurement meaning is the measurement instrument that used by people and it's still traditional. Data was received from Semparuk village, Semparuk Districts which is located in Sambas regency West Borneo. The method used in this research is descriptive and qualitative research methods. The vocabulary measurement in this research with 34 data, this study is devided into five forms of measurement that is 1) the length, width, and height, 2) lots, 3) weight, 4) volume, 5) the size of the fruit. . All of the datas consist of 15 type of measurement for length, width, and height, 6 type of meaurement for pieces, 5 type of measurement for weight, 3 type of measurement for volume, and 5 type of measurement for fruits size. Key words: Measurement, entholinguistic, computerized linguistics.